S55 Using continuous positive airway pressure (cpap) in excessive dynamic airway collapse (edac). (15th November 2016) - Hicks, AP; Brown, T; Chauhan, A; Adeniji, K; Quint, M; Babu, S
Abstract : EDAC is a term that refers to the pathological collapse of respiratory airways during expiration as a result of posterior wall muscle laxity leading to a >50% loss of airway cross-sectional area. This muscle laxity leads to a loss of airway patency which results in symptomatic dyspnoea. CPAP has been suggested as a method to ameliorate the difficulties associated with EDAC where standard medical care has failed, ameliorating the need for further invasive treatments such as endobronchial stenting or tracheoplasty. Demonstrating its effectiveness is difficult as many of those who suffer with EDAC have co-morbid disease such as COPD, asthma or EGPA which may mask the impact of CPAP when measuring response with subjective criteria such as the WHO functional impairment scale. We set out to determine whether we could objectively demonstrate improvements in airway diameter using CPAP in patients with EDAC, in addition to COPD and EGPA, using firstly bronchoscopy and secondly dynamic computed tomography (CT). In both cases we used a Philips Respironics Trilogy 200 CPAP device to deliver positive airway pressure at 5 cm increments up to a pressure of 20 cmH2O. Figure 1a shows a bronchoscopic example of this process with an increase in airway area from 1.54cm 2 to 5.35cm 2 equating to a 400% increase in volume at 20 cm H2 O. Figure 1b shows a CT example with a 52.9% increase in airway area, with the RMB increasing in diameter by 3 mm. CPAP was objectively shown to be an effective, relatively inexpensive, treatment for EDAC via bronchoscopy or CT imaging and it is hypothesised such independent measures enhance existing assessments of improvement.